Model Predictive Control - Zheng, Tao (IntechOpen, 2010)
Frontiers of Model Predictive Control Robust Model Predictive Control Nonlinear Model Predictive Control Excellent Applications Guide for Researchers and Engineers Recent Achievements of Authors over the World Theory with Practical Examples Kinds of Algorithms for Choice